Epoxy resin carbon skeleton lithium metal negative electrode and preparation method thereof, and lithium battery
Patent Information
- Application Number
- CN202611199613.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-20
AI Technical Summary
然而,锂金属在循环过程中易产生枝晶、体积膨胀剧烈、力学性能差等问题,严重制约其实际应用
1、本发明提供一种环氧树脂碳骨架锂金属负极制备方法,通过环氧树脂与固化剂混合,加入催化剂进行固化获得环氧树脂交联聚合物,再将环氧树脂交联聚合物在含有适量氧气的碳化气氛中进行碳化,经过酸洗、水洗、活化获得环氧树脂碳骨架;将锂金属与环氧树脂碳骨架按比例进行混炼处理后得到改性锂金属,并将该改性锂金属制成环氧树脂碳骨架锂金属负极。本发明的环氧树脂具有优异的粘接性、化学稳定性和可调控的交联网络,其碳化产物可以保留丰富的活性官能团,有利于提升碳骨架与锂金属的界面结合力和离子传输能力;环氧树脂中含有大量的刚性苯环,固化后形成刚性主链,环氧树脂中有丰富的环氧基,环氧树脂与固化剂反应能形成高密度的刚性三维交联网络。通过固化剂可以引入氮、硫等杂原子,实现杂原子掺杂,引入更丰富多样的活性位点,有利于提升环氧树脂碳骨架与锂金属的界面结合力和离子传输能力。本发明采用的制备方法工艺简单,只需要预固化和固化两步即可获得环氧树脂碳骨架的前驱体环氧树脂交联聚合物,对设备的要求不高,生产成本低,有利于环氧树脂碳骨架锂金属负极工业化大规模制备,环氧树脂碳骨架可适用于多种锂金属体系。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to an epoxy resin carbon skeleton lithium metal anode, its preparation method, and a lithium battery. Background Technology
[0002] Lithium metal is considered an ideal anode material for next-generation high-energy-density batteries due to its extremely high theoretical specific capacity and low electrochemical potential. However, lithium metal is prone to dendrite formation, severe volume expansion, and poor mechanical properties during cycling, which seriously restricts its practical application. Current technologies often improve the performance of lithium metal anodes by introducing carbon materials, polymer coatings, or three-dimensional frameworks, but most methods suffer from complex preparation processes, weak interfacial bonding between the carbon framework and lithium metal, and insufficient active sites.
[0003] The authorized patent CN120933292B discloses a carbon skeleton-enhanced lithium metal anode using dimethyl terephthalate and aliphatic diol as precursors. Although it has achieved certain results, its carbon source system is singular. The prepolymer only involves three elements: carbon, hydrogen, and oxygen, and three groups: methylene, phenyl, and ester. The reaction sites after carbonization are mainly concentrated on the incompletely reacted phenyl or carbon-oxygen heterocycles. The types and distribution of functional groups in the carbon skeleton are limited, and the active site types are singular. The crosslinking density of the prepolymer is low, and the carbon skeleton obtained after carbonization has limited effect on improving the tensile strength of the lithium metal anode, resulting in insufficient rigidity. Moreover, the synthesis process is complex and the overall cost is high, which is not conducive to multi-scenario adaptation. Summary of the Invention
[0004] This invention provides an epoxy resin carbon skeleton lithium metal anode with epoxy resin as a carbon precursor and its preparation method. The epoxy resin carbon skeleton with a rigid three-dimensional cross-linked network with rich and diverse active sites and high cross-linking density is prepared by carbonization of epoxy resin cross-linked polymer, and then combined with lithium metal to significantly improve the tensile strength and interfacial stability of the epoxy resin carbon skeleton lithium metal anode.
[0005] This invention provides a method for preparing an epoxy resin carbon skeleton lithium metal anode, comprising the following steps: mixing epoxy resin and curing agent at a mass ratio of 1:(0.8-1.2), adding a catalyst with a mass content of 0.2%-0.5% of the epoxy resin content, pre-curing at 80℃-120℃ for 1h-3h under an inert atmosphere, and then heating to 140℃-180℃ for further curing for 2h-5h to obtain an epoxy resin crosslinked polymer; wherein the epoxy resin includes any one or a combination of bisphenol F type epoxy resin, phenolic epoxy resin, and bisphenol A type epoxy resin; and subjecting the epoxy resin crosslinked polymer to a carbonization atmosphere. In the process, the temperature is increased to 300℃-600℃ at a heating rate of 1℃ / min-5℃ / min for 1h-4h. The carbonized product is then acid-washed with 0.1M-1M dilute nitric acid, followed by water washing. Activation is then performed at 250℃-400℃ for 1h-3h under an inert atmosphere to obtain an epoxy resin carbon skeleton. The carbonization atmosphere is a mixture of nitrogen and oxygen, with an oxygen volume fraction of 1%-5%. Modified lithium metal is obtained by mixing lithium metal and the epoxy resin carbon skeleton in a specific ratio, and the modified lithium metal is then used to fabricate an epoxy resin carbon skeleton lithium metal anode.
[0006] Furthermore, the curing agent includes any one of methyltetrahydrophthalic anhydride, diaminodiphenyl sulfone, and polyetheramine.
[0007] Furthermore, the process of mixing epoxy resin and curing agent specifically involves adding the curing agent to the epoxy resin, stirring at 100rpm-200rpm for 3min-5min, and performing degassing treatment at 100Pa-200Pa.
[0008] Furthermore, the catalyst includes any one or a combination of imidazole catalysts and amine catalysts.
[0009] Further, the lithium metal and the epoxy resin carbon skeleton are mixed in a two-roll mill at a mass ratio of (90-99):(1-10) to obtain modified lithium metal.
[0010] Furthermore, the two-roll open mill includes a front roller and a rear roller, the front roller rotates at 10 rpm to 20 rpm, the speed ratio of the front roller to the rear roller is (1.1-1.5):1; and / or, the roller gap between the front roller and the rear roller is 0.5 mm to 2 mm.
[0011] Furthermore, the mixing process is carried out at a temperature of 30℃-60℃ for a time of 10min-30min.
[0012] Furthermore, the modified lithium metal is cold-rolled into a sheet with a thickness of 0.05mm-0.5mm, and then die-cut to obtain an epoxy resin carbon skeleton lithium metal anode.
[0013] The present invention also provides an epoxy resin carbon skeleton lithium metal anode, wherein the epoxy resin carbon skeleton lithium metal anode is prepared by the epoxy resin carbon skeleton lithium metal anode preparation method described above, the epoxy resin carbon skeleton lithium metal anode comprises lithium metal and epoxy resin carbon skeleton, the mass ratio of lithium metal to epoxy resin carbon skeleton is (90-99):(1-10); and / or, the tensile strength of the epoxy resin carbon skeleton lithium metal anode is 7MPa-12MPa.
[0014] This invention further provides a lithium battery, comprising a positive electrode, an electrolyte, and an epoxy resin carbon skeleton lithium metal negative electrode as described above. Compared with the prior art, the epoxy resin carbon skeleton lithium metal negative electrode, its preparation method, and the lithium battery provided by this invention have the following beneficial effects: 1. This invention provides a method for preparing an epoxy resin carbon skeleton lithium metal anode. The method involves mixing epoxy resin with a curing agent, adding a catalyst for curing to obtain an epoxy resin crosslinked polymer, then carbonizing the epoxy resin crosslinked polymer in a carbonization atmosphere containing an appropriate amount of oxygen. After acid washing, water washing, and activation, an epoxy resin carbon skeleton is obtained. Lithium metal and the epoxy resin carbon skeleton are then mixed in a specific ratio to obtain modified lithium metal, which is then used to prepare the epoxy resin carbon skeleton lithium metal anode. The epoxy resin of this invention possesses excellent adhesion, chemical stability, and a controllable crosslinking network. Its carbonization products retain abundant active functional groups, which is beneficial for improving the interfacial bonding force and ion transport capacity between the carbon skeleton and lithium metal. The epoxy resin contains a large number of rigid benzene rings, forming a rigid main chain after curing. The epoxy resin also contains abundant epoxy groups, and the reaction between the epoxy resin and the curing agent can form a high-density rigid three-dimensional crosslinking network. The curing agent can introduce heteroatoms such as nitrogen and sulfur, achieving heteroatom doping and introducing a richer variety of active sites, which is beneficial for improving the interfacial bonding force and ion transport capacity between the epoxy resin carbon skeleton and lithium metal. The preparation method used in this invention is simple, requiring only two steps: pre-curing and curing, to obtain the epoxy resin carbon skeleton precursor epoxy resin crosslinked polymer. It has low equipment requirements and low production cost, which is conducive to the large-scale industrial preparation of epoxy resin carbon skeleton lithium metal anodes. The epoxy resin carbon skeleton is applicable to a variety of lithium metal systems.
[0015] 2. The present invention further specifies that the curing agent includes any one of methyltetrahydrophthalic anhydride, diaminodiphenyl sulfone, and polyetheramine. Epoxy resin itself is an oligomer and requires a curing agent to form a rigid three-dimensional cross-linked network. Methyltetrahydrophthalic anhydride, as an anhydride curing agent, introduces abundant oxygen-containing active sites into the carbon skeleton of epoxy resin. The anhydride groups react with the hydroxyl groups of epoxy resin to generate ester bonds and carboxyl groups, forming a three-dimensional network with high cross-linking density. Diaminodiphenyl sulfone, as a curing agent, can introduce nitrogen and sulfur dual heteroatom doping and enhance the rigidity and heat resistance of the epoxy resin carbon skeleton. Polyetheramine can introduce flexible segments to improve the toughness of the epoxy resin carbon skeleton and form a porous structure through its violent thermal decomposition.
[0016] 3. The present invention further specifies that in step S1, the process of mixing the epoxy resin and the curing agent specifically involves adding the curing agent to the epoxy resin, stirring at 100 rpm-200 rpm for 3-5 minutes, and performing degassing treatment at 100 Pa-200 Pa. Stirring at a low speed of 100 rpm-200 rpm reduces bubble formation. Degassing at 100 Pa-200 Pa causes dissolved air and suspended microbubbles in the epoxy resin-curing agent reaction system to expand, rise, and burst, expelling the gas from the reaction system. The epoxy resin-curing agent reaction system formed through the above mixing steps is uniform and bubble-free, which is beneficial for forming a uniform epoxy resin carbon skeleton with high crosslinking density during subsequent carbonization.
[0017] 4. In the technical solution of the present invention, the catalyst used includes any one or more combinations of imidazole catalysts and amine catalysts. The catalyst can efficiently promote the ring-opening reaction of the epoxy groups of epoxy resin, effectively reduce the activation energy of the reaction, and shorten the curing time. Imidazole catalysts react slowly with epoxy resin at room temperature, but can catalyze the reaction rapidly at medium and high temperatures of 140℃-180℃. Amine catalysts enable the system to catalyze the reaction rapidly at room temperature or lower temperatures, significantly shortening the curing time.
[0018] 5. The present invention further specifies that lithium metal and the epoxy resin carbon skeleton are mixed in a two-roll mill at a mass ratio of (90-99):(1-10). Under this mass ratio, the lithium metal content is dominant, and the obtained epoxy resin carbon skeleton lithium metal anode can maintain the ductility and conductivity of the metal. If the epoxy resin carbon skeleton content is too low, relying solely on the toughness of lithium metal itself to improve the elongation at break will lead to a decrease in the hardness of the epoxy resin carbon skeleton lithium metal anode, and thus a decrease in tensile strength. As a reinforcing phase, the epoxy resin carbon skeleton significantly improves the tensile strength of the epoxy resin carbon skeleton lithium metal anode.
[0019] 6. In the technical solution of the present invention, the front roller speed of the two-roll open mill is further defined as 10 rpm-20 rpm, the speed ratio of the front roller to the rear roller is (1.1-1.5):1, and the roller gap between the front roller and the rear roller is 0.5 mm-2 mm. Through the control of the roller gap and speed during the above mixing process, the lithium metal and the epoxy resin carbon skeleton are uniformly compounded to form a tightly bonded interface. External force can be uniformly transmitted in the obtained epoxy resin carbon skeleton lithium metal anode, thereby improving the tensile strength and elongation at break of the epoxy resin carbon skeleton lithium metal anode.
[0020] 7. In the technical solution of the present invention, the mixing temperature is further defined as 30℃-60℃ and the time is 10min-30min. When the mixing is carried out at 30℃-60℃, the lithium metal softens. The mixing temperature does not exceed 60℃, which can effectively avoid the oxidation of the lithium metal surface and prevent the lithium-affinity reactive sites of the carbon skeleton from decomposing prematurely or undergoing unnecessary interfacial reactions with the lithium metal due to high temperature.
[0021] 8. In the technical solution of the present invention, the modified lithium metal is cold-rolled into a sheet with a thickness of 0.05mm-0.5mm, and then die-cut to obtain an epoxy resin carbon skeleton lithium metal anode. The thickness of 0.05mm-0.5mm can match high energy density lithium batteries, reduce the volume ratio of the anode, reserve more space for active cathode materials, and improve the overall energy density of the lithium battery.
[0022] 9. This invention also provides an epoxy resin carbon skeleton lithium metal anode, which is prepared by the method described above. The epoxy resin carbon skeleton lithium metal anode comprises lithium metal and an epoxy resin carbon skeleton, with a mass ratio of lithium metal to epoxy resin carbon skeleton of (90-99):(1-10); and / or, the tensile strength of the epoxy resin carbon skeleton lithium metal anode is 7MPa-12MPa. The addition of the epoxy resin carbon skeleton can improve the tensile strength of the epoxy resin carbon skeleton lithium metal anode, thereby significantly improving its processing performance. The epoxy resin carbon skeleton lithium metal anode exhibits excellent volume adaptability and dendrite suppression ability during cycling, which can significantly improve battery cycle life. The epoxy resin carbon skeleton has abundant reaction sites containing oxygen and nitrogen that can combine with lithium metal, providing stronger adsorption and nucleation induction capabilities for lithium ions, making the interfacial bonding of the finally obtained epoxy resin carbon skeleton lithium metal anode more stable, and its mechanical properties are optimized.
[0023] 10. The present invention further provides a lithium battery, the lithium battery comprising a positive electrode, an electrolyte and an epoxy resin carbon skeleton lithium metal negative electrode as described above, the lithium battery having stable cycle performance, the epoxy resin carbon skeleton lithium metal negative electrode having a rigid three-dimensional network, so that the epoxy resin carbon skeleton lithium metal negative electrode can still remain intact under the non-compression action of external force, thereby maintaining the integrity of the electrode structure and extending the cycle life of the lithium battery. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a flowchart illustrating the specific steps of a method for preparing an epoxy resin carbon skeleton lithium metal anode provided in the first embodiment of the present invention.
[0026] Figure 2 This is a flowchart illustrating the specific steps of step S3 in the preparation method of an epoxy resin carbon skeleton lithium metal anode provided in the first embodiment of the present invention.
[0027] Figure 3 A schematic diagram of the structure of a lithium battery provided in the third embodiment of the present invention.
[0028] Explanation of reference numerals in the attached diagram: 10. Lithium battery; 11. Epoxy resin carbon skeleton lithium metal anode; 12. Positive electrode; 13. Solid electrolyte; 14. Casing. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0030] In the embodiments provided by this invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined based on A. However, it should also be understood that determining B based on A does not mean determining B solely based on A; B can also be determined based on A and / or other information.
[0031] It should be understood that the phrase "one embodiment" or "an embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of the invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Those skilled in the art should also recognize that the embodiments described in the specification are optional embodiments, and the actions and modules involved are not necessarily essential to the invention.
[0032] In various embodiments of the present invention, it should be understood that the sequence number of each process does not necessarily imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0033] The flowcharts and block diagrams in the accompanying drawings illustrate methods and possible architectures, functions, and operations according to various embodiments of this application. In this regard, each block in the flowchart or block diagram may represent part of a step. It should also be noted that in some alternative implementations, the functions indicated in the blocks may occur in a different order than those indicated in the drawings. For example, two consecutively indicated blocks may actually be executed substantially in parallel, or they may sometimes be executed in reverse order, depending on the functions involved.
[0034] Please see Figure 1 The first embodiment of the present invention provides a method for preparing an epoxy resin carbon skeleton lithium metal anode, specifically including the following steps: S1. Mix epoxy resin and curing agent at a mass ratio of 1:(0.8-1.2), add catalyst with a mass content of 0.2%-0.5% of epoxy resin, pre-cur at 80℃-120℃ for 1h-3h under an inert atmosphere, and then heat to 140℃-180℃ for 2h-5h to obtain epoxy resin crosslinked polymer; wherein, the epoxy resin includes any one or a combination of bisphenol F type epoxy resin, phenolic epoxy resin, and bisphenol A type epoxy resin; S2. The epoxy resin crosslinking polymer is carbonized in a carbonizing atmosphere at a heating rate of 1℃ / min-5℃ / min to 300℃-600℃ for 1h-4h. The carbonized product is acid-washed with 0.1M-1M dilute nitric acid, then washed with water, and activated at 250℃-400℃ for 1h-3h in an inert atmosphere to obtain the epoxy resin carbon skeleton; wherein the carbonizing atmosphere is a mixture of nitrogen and oxygen, and the volume fraction of oxygen in the mixture is 1%-5%; and S3. Modified lithium metal is obtained by mixing lithium metal with epoxy resin carbon skeleton in a certain proportion, and the modified lithium metal is made into epoxy resin carbon skeleton lithium metal anode.
[0035] Specifically, in step S1, the epoxy resin includes any one or a combination of bisphenol F type epoxy resin, phenolic epoxy resin, and bisphenol A type epoxy resin; the curing agent includes any one of methyltetrahydrophthalic anhydride, diaminodiphenyl sulfone, and polyetheramine, where methyltetrahydrophthalic anhydride is an acid anhydride curing agent, and diaminodiphenyl sulfone and polyetheramine are amine curing agents. The epoxy resin and curing agent used in this invention contain elements such as carbon, hydrogen, oxygen, nitrogen, and sulfur, and contain epoxy groups, phenolic hydroxyl groups, ether bonds, benzene rings, acid anhydride groups, amino groups, and sulfone groups, which can introduce a rich variety of active sites. Epoxy resin has excellent adhesion, chemical stability, and a controllable crosslinking network. Its carbonization products can retain a rich variety of active functional groups, which is beneficial to improving the interfacial bonding force between the carbon skeleton and lithium metal. Epoxy resin contains a large number of rigid benzene rings, which form a rigid main chain after curing. Epoxy resin has abundant epoxy groups, and the reaction between epoxy resin and curing agent can form a high-density rigid three-dimensional crosslinking network. Curing agents can be used to introduce heteroatoms such as nitrogen and sulfur, achieving heteroatom doping and introducing a richer and more diverse range of active sites.
[0036] In step S1 above, the epoxy groups in the epoxy resin undergo ring-opening under the induction of the curing agent and catalyst, and cross-link with the active groups of the curing agent, gradually constructing a rigid three-dimensional cross-linked network from liquid small molecules. The epoxy resin-curing agent system of this invention is used to prepare an epoxy resin carbon skeleton. The epoxy resin carbon skeleton formed after carbonization has a rich variety of active sites, which are effective lithiophilic sites, helping to enhance the interfacial bonding between the epoxy resin carbon skeleton and lithium metal. The epoxy resin carbon skeleton has a high-density rigid three-dimensional cross-linked network, good structural stability, and high tensile strength.
[0037] Specifically, in step S1 above, epoxy resin and curing agent are mixed at a mass ratio of 1:(0.8-1.2). In some embodiments of the present invention, the mass ratio of epoxy resin to curing agent can be 1:(0.8-0.9), 1:(0.9-1.0), 1:(1.0-1.1), 1:(1.1-1.2), etc.; in some specific embodiments of the present invention, it can be 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, etc. At this mass ratio, the curing agent can fully react with the epoxy groups of the epoxy resin to form a dense, rigid three-dimensional cross-linked network structure. Different ratios can adjust the cross-linking density of the epoxy resin carbon skeleton. The rigid three-dimensional cross-linked network structure is key to the subsequent carbonization to form the epoxy resin carbon skeleton, which is beneficial for maintaining its shape during subsequent high-temperature carbonization. The higher the cross-linking density, the stronger the rigidity of the epoxy resin carbon skeleton and the higher the tensile strength, but the smaller the molecular chain mobility space and the lower the elongation at break. An imbalance in the ratio of epoxy resin to curing agent can lead to incomplete or excessive cross-linking, resulting in defects in the epoxy resin carbon skeleton, increased brittleness, and a simultaneous deterioration in tensile strength and elongation at break.
[0038] Specifically, in step S1, the process of mixing epoxy resin and curing agent involves adding the curing agent to the epoxy resin and stirring at 100-200 rpm for 3-5 minutes; then performing degassing treatment at 100-200 Pa until no more bubbles are released, thus completing the degassing process. Stirring at a low speed of 100-200 rpm reduces bubble formation. High-speed stirring generates strong eddies and surface disturbances, easily entraining air into the epoxy resin-curing agent reaction system, forming bubbles. These bubbles will transform into cracks within the epoxy resin carbon skeleton during subsequent carbonization, weakening the mechanical strength of the epoxy resin carbon skeleton. Degassing at 100-200 Pa causes dissolved air and suspended microbubbles in the epoxy resin-curing agent reaction system to expand, rise, and burst, expelling the gas from the reaction system.
[0039] Specifically, in step S1, the epoxy resin and curing agent are mixed and stirred at 100 rpm-200 rpm for 3-5 minutes, followed by degassing at 100 Pa-200 Pa. In some embodiments of the present invention, the mixing speed can be further 105 rpm-118 rpm, 115 rpm-120 rpm, 135 rpm-150 rpm, 160 rpm-200 rpm, etc.; in some specific embodiments of the present invention, the mixing speed can be specifically 106 rpm, 125 rpm, 130 rpm, 155 rpm, 190 rpm, etc. In some embodiments of the present invention, the degassing pressure can be further 112 Pa-128 Pa, 136 Pa-148 Pa, 170 Pa-185 Pa, 176 Pa-195 Pa, etc.; in some specific embodiments of the present invention, the degassing pressure can be specifically 116 Pa, 130 Pa, 146 Pa, 154 Pa, 185 Pa, etc.
[0040] Specifically, in step S1, after the epoxy resin and curing agent are mixed, a catalyst with a mass content of 0.2%-0.5% of the epoxy resin content is added. In some embodiments of the present invention, the amount of catalyst added is 0.2%-0.3%, 0.25%-0.35%, 0.3%-0.4%, 0.4%-0.5% of the epoxy resin mass content, etc.; in some specific embodiments of the present invention, the amount of catalyst added is 0.2%, 0.25%, 0.3%, 0.4%, 0.5% of the epoxy resin mass content, etc. This amount of catalyst can prevent the reaction from being too fast, leading to local overheating or uneven curing, making the curing process stable and controllable, and obtaining a uniformly structured epoxy resin crosslinked polymer. Further, the catalyst includes any one or more combinations of imidazole catalysts and amine catalysts. In some specific embodiments of the present invention, it may specifically be 2-ethyl-4-methylimidazolium.
[0041] Specifically, in step S1, after adding the catalyst, pre-curing is performed at 80℃-120℃ for 1-3 hours under an inert atmosphere. In some embodiments of the present invention, the pre-curing temperature is 80℃-90℃, 85℃-95℃, 90℃-100℃, 110℃-120℃, etc.; in some specific embodiments of the present invention, the pre-curing temperature is 80℃, 85℃, 90℃, 100℃, 110℃, 120℃, etc. In some embodiments of the present invention, the pre-curing time is 1h-2h, 1.5h-2.5h, 2h-3h, 2.5h-3h, etc.; in some specific embodiments of the present invention, the pre-curing time can specifically be 1h, 1.5h, 2h, 3h, etc.
[0042] During the pre-curing stage, the molecular chains in the epoxy resin and curing agent reaction system are actively moving, allowing the curing agent and catalyst to fully diffuse and contact the epoxy groups of the epoxy resin, achieving molecular-level mixing and reaction. The epoxy groups of the epoxy resin and the active groups of the curing agent begin a slow cross-linking reaction during the pre-curing stage, resulting in a rapid increase in molecular weight and the formation of linear or slightly branched prepolymers. At this stage, a low-crosslinking, rigid three-dimensional cross-linked network is initially formed. Pre-curing at 80℃-120℃ allows the epoxy resin and curing agent to begin the cross-linking reaction under mild conditions. At this temperature, the viscosity of the reaction system decreases, which is beneficial for the uniform mixing of reactant components. This avoids uneven local curing agent concentration and ensures a uniform final cross-linked network structure.
[0043] Specifically, in step S1 above, after pre-curing is completed, the temperature is raised to 140℃-180℃ and cured for another 2-5 hours. In some embodiments of the present invention, the temperature can be raised to 140℃-145℃, 150℃-160℃, 160℃-170℃, 165℃-175℃, 170℃-180℃, etc.; in some specific embodiments of the present invention, the temperature can be raised to 140℃, 145℃, 150℃, 160℃, 165℃, 175℃, 180℃, etc. The curing time can be 2-3 hours, 2.5-3.5 hours, 3-4 hours, 4.5-5 hours, etc., specifically 2 hours, 2.2 hours, 3 hours, 3.5 hours, 4 hours, 4.8 hours, 5 hours, etc. Pre-curing followed by further curing allows unreacted groups to fully react, enabling the epoxy resin crosslinked polymer to form a stable, high-density crosslinked network. Continuing curing at 140℃-180℃ can improve the thermal stability of the epoxy resin crosslinked polymer, maintaining structural integrity and reducing deformation during subsequent carbonization.
[0044] As the crosslinking reaction between epoxy resin and curing agent proceeds, the molecular weight and crosslinking density of the prepolymer gradually increase, and its glass transition temperature also rises accordingly. Controlling the temperature within the relatively low range of 80℃-120℃ during the pre-curing stage allows the molecular chains to maintain a certain degree of mobility during curing, releasing internal stress generated during the reaction in a timely manner and preventing cracks from forming due to stress concentration. If epoxy resin and curing agent are directly cured at 140℃-180℃, the glass transition temperature rises. When the glass transition temperature approaches the curing temperature, a large number of active groups are frozen before they can react, resulting in incomplete reaction. In this invention, a preliminary rigid three-dimensional crosslinking network is first established at 80℃-120℃, and then the temperature is raised to 140℃-180℃, allowing the reaction system to adapt slowly. The glass transition temperature rises, allowing the active groups frozen during the pre-curing stage to continue the crosslinking reaction, constructing a rigid three-dimensional crosslinking network with high crosslinking density.
[0045] Specifically, in step S1, the epoxy resin and curing agent are fully reacted by precisely controlling the stoichiometric ratio of the reactants and the amount of catalyst to form a dense, rigid three-dimensional cross-linked network structure. By segmented curing and controlling the temperature and time of segmented curing, a cross-linked epoxy resin polymer with uniform structure, high cross-linking density and good thermal stability is prepared, laying the foundation for obtaining a high-performance epoxy resin carbon skeleton in the carbonization step.
[0046] Specifically, in step S2 above, the epoxy resin crosslinked polymer is heated to 300℃-600℃ in a carbonization atmosphere at a heating rate of 1℃ / min-5℃ / min for 1h-4h. Specifically, the heating rate can be 1℃ / min-2℃ / min, 1.5℃ / min-2.5℃ / min, 2℃ / min-3℃ / min, 3.2℃ / min-4.5℃ / min, 4℃ / min-5℃ / min, etc. In some specific embodiments of the present invention, the heating rate can be 1℃ / min, 1.2℃ / min, 2.8℃ / min, 3℃ / min, 4.5℃ / min, 5℃ / min, etc. Specifically, the temperature can be raised to 300℃-340℃, 380℃-400℃, 450℃-500℃, 480℃-560℃, 500℃-600℃, etc.; in some specific embodiments of the present invention, the temperature can be raised to 300℃, 320℃, 360℃, 440℃, 480℃, 500℃, 600℃, etc.
[0047] Specifically, in step S2, the carbonization time can be 1h-1.5h, 2h-3h, 2.5h-3.8h, 3.2h-4h, 3.8h-4h, etc.; the carbonization time can be further specified as 1h, 1.2h, 2.8h, 3h, 4h, etc.
[0048] Specifically, during the carbonization process in step S2, a slow heating rate of 1℃ / min-5℃ / min allows the epoxy resin crosslinked polymer sufficient time for rearrangement and polycondensation, gradually adapting to the heating process. Slow heating also prevents the formation of bubbles that could damage the carbon structure, maintaining the integrity of the epoxy resin carbon skeleton. If the temperature is raised to a high level instantaneously, the oxygen- and nitrogen-containing groups in the epoxy resin crosslinked polymer will rapidly decompose and volatilize due to localized overheating; slow heating allows these groups to anchor at the carbon layer edges, remaining in a stable form and forming active sites that coordinate with lithium ions.
[0049] Specifically, in step S2, the carbonization process is carried out by slowly heating to 300℃-600℃ for 1-4 hours. During this carbonization, the epoxy resin crosslinked polymer undergoes pyrolysis, and some nitrogen, sulfur, and oxygen elements in the polymer escape in gaseous form, forming numerous micropores in the carbon matrix. Unexposed carbon elements form graphite-like carbon materials, while unexposed nitrogen, sulfur, and oxygen heteroatoms anchor at defects and edges of the carbon skeleton, constructing chemically active sites. During carbonization, the epoxy resin crosslinked polymer transforms from an organic polymer into an inorganic carbon material with a microporous structure and specific chemical activity, constructing an epoxy resin carbon skeleton. The medium-low temperature of 300℃-600℃ ensures that most of the nitrogen, sulfur, and oxygen heteroatoms introduced by the curing agent remain in the epoxy resin carbon skeleton, forming abundant lithium-affinity active sites and enhancing the wettability and chemical affinity for lithium metal. If the carbonization temperature is too low, it may lead to incomplete carbonization, leaving a large amount of organic components in the carbonization products, resulting in a loose carbon skeleton structure in the epoxy resin and a decrease in tensile strength. If the carbonization temperature is too high, it may lead to graphitization of the carbon structure, making the structure hard and brittle.
[0050] A carbonization time of 1-4 hours ensures that the epoxy resin crosslinking compound is fully carbonized without excessive pyrolysis. If the carbonization time is too short, such as less than 1 hour, the epoxy resin crosslinking polymer may not fully pyrolyze, leaving behind a large amount of residual organic components, which can cause the epoxy resin carbon skeleton to shrink and crack upon cooling. An excessively long carbonization time reduces the active sites at the edges of the epoxy resin carbon skeleton, decreasing the interaction between the epoxy resin carbon skeleton and lithium metal.
[0051] Specifically, in step S2, the carbonization atmosphere is a mixture of nitrogen and oxygen, and the volume fraction of oxygen in the mixture is 1%-5%. In some embodiments of the present invention, the volume fraction of oxygen in the carbonization atmosphere is 1%-1.6%, 2.5%-3%, 3.2%-4%, 3.6%-4.2%, 4%-5%, etc.; in some specific embodiments of the present invention, the volume fraction of oxygen in the carbonization atmosphere is 1%, 1.5%, 2%, 3.8%, 4.4%, 5%, etc.
[0052] A trace amount of oxygen (1%-5%) creates a mild oxidizing atmosphere. This trace oxygen alters the surface functional groups, pore structure, and interfacial interactions of the epoxy resin carbon skeleton, thereby affecting the mechanical and electrochemical performance of the epoxy resin carbon skeleton lithium metal anode. Oxygen does not deeply etch the epoxy resin carbon skeleton; instead, it selectively retains and activates active sites such as hydroxyl, carboxyl, ether bonds, and nitrogen-containing polar groups on the carbon surface, enhancing the interfacial bonding between the epoxy resin carbon skeleton and lithium metal and preventing phase delamination. The epoxy resin crosslinking polymer itself has abundant oxygen- and nitrogen-containing functional groups. If inert carbonization with pure nitrogen is used, a large number of oxygen- and nitrogen-containing groups are directly removed and decomposed at high temperatures, resulting in a significant reduction in the number of surface functional groups on the epoxy resin carbon skeleton. Byproducts easily clog newly formed micropores or deposit as amorphous carbon on the surface. Polar functional groups break, resulting in a dense and brittle epoxy resin carbon skeleton structure with reduced tensile strength and elongation at break. Trace amounts of oxygen can retain functional groups, optimize pore structure, and modify the microstructure of carbon, thereby improving the performance of epoxy resin carbon skeleton and significantly enhancing the mechanical properties and cycle life of epoxy resin carbon skeleton lithium metal anodes.
[0053] Specifically, during the carbonization process, the epoxy resin crosslinked polymer generates a large amount of volatile small molecule gas. The small molecule gas is released rapidly to form a large number of micropores, and at the same time, structural reconstruction occurs to build a carbon skeleton. Trace amounts of oxygen participate in the oxidation reaction and regulate the reactive sites on the surface of the epoxy resin carbon skeleton.
[0054] Specifically, in step S2, after carbonization, the carbonized product is acid-washed with dilute nitric acid of concentration 0.1M-1M, and the carbonized product is soaked in dilute nitric acid for 3-5 hours; after acid washing, it is washed with deionized water to remove residual acid from the carbonized product. 0.1M-1M dilute nitric acid specifically refers to dilute nitric acid with a concentration of 0.1mol / L-1mol / L, where "M" represents mol / L. Further, the concentration of dilute nitric acid can be 0.1M-0.2M, 0.26M-0.5M, 0.4M-0.6M, 0.3M-0.8M, 0.6M-1M, etc.; the specific concentration of dilute nitric acid can be 0.1M, 0.2M, 0.26M, 0.55M, 0.68M, 0.85M, 1M, etc. Furthermore, the pickling time can be 3h-3.4h, 3.8h-4h, 4.2h-4.8h, 4.6h-5h, etc.; the specific pickling time can be 3h, 3.2h, 3.5h, 4.3h, 5h, etc.
[0055] Specifically, in step S2, the carbonized product is acid-washed with 0.1M-1M dilute nitric acid. This removes impurities remaining from the carbonization process, which may induce uneven growth of lithium dendrites and increase interfacial impedance. The purified surface significantly improves the cycle stability and safety of the epoxy resin carbon skeleton. 0.1-1M dilute nitric acid has strong oxidizing properties, which can corrode the amorphous carbon regions with poor thermal stability in the epoxy resin carbon skeleton, opening up some of the originally closed micropores in the carbon skeleton. This effectively increases the specific surface area and pore volume of the epoxy resin carbon skeleton, providing more sites for subsequent lithium ion binding and effectively buffering the volume expansion of lithium metal during charge-discharge cycles, thereby improving the coulombic efficiency and cycle life of the lithium battery.
[0056] In step S2, the carbonized product is acid-washed and water-washed, then activated at 250℃-400℃ for 1-3 hours to obtain an epoxy resin carbon skeleton. In some embodiments of the present invention, the activation temperature is 250℃-280℃, 300℃-350℃, 360℃-380℃, 260℃-340℃, 370℃-400℃, etc.; further, the activation temperature can specifically be 250℃, 255℃, 325℃, 350℃, 390℃, 400℃, etc. In some embodiments of the present invention, the activation time is 1h-1.5h, 1.6h-1.8h, 2h-2.5h, 2.8h-3h, etc.; further, the activation time can specifically be 1h, 1.4h, 1.7h, 2.3h, 2.8h, 3h, etc. The carbon layer immediately after carbonization has high internal stress. Heating it at 250℃-400℃ allows for slight relaxation, eliminating internal stress and making the framework structure more stable. At this temperature, the residual oxygen in the epoxy resin carbon framework undergoes a mild oxidation reaction, regenerating oxygen-containing functional groups on the carbon layer surface. These functional groups can form strong coordination with lithium ions, enhancing the lithium affinity of the epoxy resin carbon framework. Activation for 0.5h-3h can complete surface chemical modification without damaging the bulk structure of the epoxy resin carbon framework.
[0057] Specifically, please refer to Figure 2 In step S3 above, the specific steps of mixing lithium metal with epoxy resin carbon skeleton in a certain proportion to obtain modified lithium metal, and then making the modified lithium metal into epoxy resin carbon skeleton lithium metal anode, may further include: Step S31: Lithium metal and epoxy resin carbon skeleton are mixed at a mass ratio of (90-99):(1-10) and then kneaded to obtain modified lithium metal; and In step S32, the modified lithium metal is cold-rolled into a sheet with a thickness of 0.05mm-0.5mm, and then die-cut to obtain an epoxy resin carbon skeleton lithium metal anode.
[0058] In step S31 above, specifically, the mass ratio of lithium metal to epoxy resin carbon skeleton can be 90:10-95:5, 90:10-93:7, or 93:7-99:1. Further, the specific mass ratio of lithium metal to epoxy resin carbon skeleton is 90:10, 91:9, 93:7, 95:5, 96:4, 97:3, and 99:1. At this mass ratio, lithium metal content is dominant, and the obtained modified lithium metal retains the ductility and conductivity of the metal, making it easy to roll and form. Simultaneously, the carbon skeleton accounts for 1%-10%, forming a three-dimensional network. The carbon skeletons overlap, effectively bearing the load without causing the material to become brittle or difficult to mix due to excessive carbon. If the proportion of epoxy resin carbon skeleton is too high, the hardness and brittleness of the final epoxy resin carbon skeleton lithium metal anode are enhanced, the tensile strength increases, the proportion of flexible lithium phase decreases, the overall ductility of the epoxy resin carbon skeleton lithium metal anode deteriorates, and the elongation at break decreases. If the proportion of epoxy resin carbon skeleton is too low, relying solely on the toughness of lithium metal itself to improve the elongation at break will lead to a decrease in the hardness of the epoxy resin carbon skeleton lithium metal anode and a decrease in the tensile strength of the epoxy resin carbon skeleton lithium metal anode.
[0059] Specifically, in step S31, a mixing process is carried out in a two-roll mill. The mixing temperature of the two-roll mill is 30℃-60℃. The two-roll mill includes a front roll and a rear roll, with a roll gap of 0.5mm-2mm. The front roll speed is 10rpm-20rpm, and the speed ratio of the front roll to the rear roll is (1.1-1.5):1. The mixing time is 10min-30min.
[0060] Specifically, the two-roll open mill includes a front roller and a rear roller, which rotate at different speeds, thereby generating strong shearing force. In this invention, the front roller rotates at 10-20 rpm, and the speed ratio of the front roller to the rear roller is (1.1-1.3):1. Specifically, the speed ratio of the front roller to the rear roller can be 1.1:1, 1.15:1, 1.2:1, 1.21:1, 1.26:1, 1.29:1, and 1.3:1, etc., and can be adjusted according to the mixing requirements.
[0061] Specifically, the front wheel speed can also be 10rpm-15rpm, 12rpm-16rpm, 14rpm-20rpm, and 13rpm-18rpm. The specific front wheel speed can be 10rpm, 12rpm, 15rpm, 16rpm, 17rpm, 18rpm, 19rpm, or 20rpm, where rpm represents revolutions per minute.
[0062] In step S31, the mixing temperature is 30℃-60℃, and can be further set to 30℃-35℃, 35℃-48℃, 45℃-50℃, 50℃-60℃, etc. Specific mixing temperatures can also be 30℃, 32℃, 38℃, 40℃, 45℃, 55℃, 60℃, etc. Mixing at 30℃-60℃ softens the lithium metal. A mixing temperature not exceeding 60℃ effectively prevents oxidation of the lithium metal surface and also prevents premature decomposition of the lithium-affinity reactive sites in the carbon skeleton or unnecessary interfacial reactions with the lithium metal due to high temperatures. Under shear force, the lithium metal embeds into the micropores and gaps of the epoxy resin carbon skeleton, achieving physical bonding. After embedding into the epoxy resin carbon skeleton, the lithium metal reacts chemically with the active sites on the inner walls of the micropores and gaps of the epoxy resin carbon skeleton, achieving chemical bonding. In the final epoxy resin carbon skeleton lithium metal anode, lithium metal is embedded and filled in the epoxy resin carbon skeleton as a continuous matrix, ensuring rapid and continuous conduction of ions and electrons; the epoxy resin carbon skeleton, as a uniform skeleton structure in the lithium metal matrix, provides strength support for the lithium metal.
[0063] To better control the progress of the two-roll mixing process, the roll gap between the front and rear rollers is set to 0.5mm-2mm. Further, the roll gap can be 0.8mm-1.5mm, 0.5mm-1.2mm, or 1mm-2mm. Specifically, the roll gap can be 0.5mm, 1mm, 1.5mm, or 2mm.
[0064] In step S31, the mixing process takes 10-30 minutes. Specifically, the mixing time can also be 10-25 minutes, 15-30 minutes, or 18-24 minutes. Further, the specific mixing time can also be 10 minutes, 15 minutes, 18 minutes, 20 minutes, 24 minutes, 28 minutes, or 30 minutes.
[0065] It is understood that in other embodiments of the present invention, step S31 can also be performed using other types of mixing equipment to mix lithium metal and epoxy resin carbon skeleton at a mass ratio of (90-99):(1-10) to obtain modified lithium metal. However, the modified lithium metal obtained by the mixing process using a two-roll mill has the best performance. By controlling the mixing temperature, roll gap, rotation speed, and mixing time during the above mixing process, the lithium metal and epoxy resin carbon skeleton are uniformly compounded to form a tightly bonded interface. External force can be uniformly transmitted within the obtained epoxy resin carbon skeleton lithium metal anode, thereby improving the tensile strength and elongation at break of the epoxy resin carbon skeleton lithium metal anode.
[0066] Specifically, in step S32 above, the modified lithium metal can be prepared by cold rolling. The cold rolling temperature corresponding to the sheet material is room temperature or below room temperature, such as 25℃, 20℃, 18℃, 15℃, 10℃, 5℃, 3℃, or 0℃.
[0067] It is understood that the modified lithium metal with good processing performance has been obtained through the mixing in step S31, and in the subsequent step S32, only the thickness and size of the modified lithium metal are adjusted. In some specific embodiments of the present invention, mirror rolls are used, and the cold rolling temperature is as defined above. The thickness of the sheet after the modified lithium metal passes through the rolls can be 0.5mm-5mm, and the rolling speed is 0.1m / s-5m / s. The specific sheet thickness and cold rolling speed can be adjusted based on the actual size and thickness requirements of the epoxy resin carbon skeleton lithium metal anode to be formed, as well as the application of molding materials, etc. The above content is only an example.
[0068] It is understood that in some other specific embodiments, after obtaining modified lithium metal in step S31, the modified lithium metal is then made into the desired epoxy resin carbon skeleton lithium metal anode. The subsequent steps can be replaced by other methods, such as making epoxy resin carbon skeleton lithium metal anode by hydrostatic pressing, molding, etc.
[0069] To further meet the needs of different lithium battery applications, epoxy resin carbon skeleton lithium metal anodes can be cut into any irregular shape through die-cutting, and can also be further combined with curved batteries or flexible batteries for fabrication.
[0070] In this invention, the tensile strength of the epoxy resin carbon skeleton lithium metal anode prepared in steps S1-S3 of the above-mentioned epoxy resin carbon skeleton lithium metal anode preparation method can reach 7 MPa-12 MPa. Compared with the unmodified epoxy resin carbon skeleton lithium metal anode (tensile strength of about 1.4 MPa) and the epoxy resin carbon skeleton lithium metal anode modified with dimethyl terephthalate and aliphatic diol (tensile strength of 6.2 MPa-8.7 MPa), the tensile strength of the lithium metal prepared by this invention is significantly improved, and it has better mechanical properties.
[0071] In this invention, the epoxy resin carbon skeleton has a significant effect on improving the tensile strength of the epoxy resin carbon skeleton lithium metal anode. Through the structural design of the epoxy resin crosslinking polymer, this invention successfully prepared an epoxy resin carbon skeleton with abundant active sites and a high crosslinking density, forming a rigid three-dimensional crosslinked network. The epoxy resin carbon skeleton is then mixed with lithium metal to prepare the epoxy resin carbon skeleton lithium metal anode. The bonding of the epoxy resin carbon skeleton can improve the tensile strength of the epoxy resin carbon skeleton lithium metal anode, thereby significantly enhancing its structural stability and improving the service life of lithium batteries with this epoxy resin carbon skeleton lithium metal anode. The preparation method used in this invention is simple, requires low-end equipment, and has low production costs, which is conducive to the large-scale industrial production of epoxy resin carbon skeleton lithium metal anodes.
[0072] The second experimental example of the present invention is an epoxy resin carbon skeleton lithium metal anode, which is prepared by the epoxy resin carbon skeleton lithium metal anode preparation method as described in the first embodiment above.
[0073] In the epoxy resin carbon skeleton lithium metal anode of the present invention, the mass ratio of lithium metal to epoxy resin carbon skeleton is (90-99):(1-10). Further, the mass ratio of lithium metal to epoxy resin carbon skeleton can also be (90-95):(5-10), (95-97):(3-5), (92-98):(2-8), etc.; specifically, the mass ratio of lithium metal to epoxy resin carbon skeleton is 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, or 99:1, etc. The tensile strength of the epoxy resin carbon skeleton lithium metal anode can reach 7 MPa-12 MPa, showing a significant improvement in tensile strength and superior mechanical properties. In the epoxy resin carbon skeleton lithium metal anode, lithium metal content is dominant, ensuring that the obtained epoxy resin carbon skeleton lithium metal anode retains the ductility and conductivity of the metal; the epoxy resin carbon skeleton, as a reinforcing phase, significantly improves the tensile strength of the epoxy resin carbon skeleton lithium metal anode.
[0074] The epoxy resin carbon framework lithium metal anode of this invention exhibits excellent volume adaptability and dendrite suppression during cycling, significantly improving battery cycle life. An epoxy resin carbon framework with abundant active sites and a high crosslinking density is prepared using an epoxy resin crosslinking polymer. The epoxy resin carbon framework possesses abundant oxygen- and nitrogen-containing reaction sites that can bind to lithium metal, enhancing the interfacial bonding between the epoxy resin carbon framework and lithium metal. The high crosslinking density of the rigid three-dimensional crosslinking network improves the tensile strength and structural stability of the epoxy resin carbon framework lithium metal anode, achieving synergistic optimization of strength and rigidity. The preparation of the epoxy resin carbon framework using epoxy resin crosslinking polymers involves introducing nitrogen and sulfur heteroatoms into the carbon framework through nitrogen- and sulfur-containing curing agents. This expands the active sites from a single oxygen element to a synergistic effect of oxygen, nitrogen, and sulfur, providing stronger adsorption and nucleation induction capabilities for lithium ions, resulting in a more stable interfacial bonding of the final epoxy resin carbon framework lithium metal anode.
[0075] In the epoxy resin carbon skeleton lithium metal anode of this invention, the epoxy resin carbon skeleton acts as a three-dimensional reinforcement, achieving stress transfer through interfacial interactions. This transfers most of the applied tensile load to the carbon skeleton, significantly improving the tensile strength of the epoxy resin carbon skeleton lithium metal anode. The rigid three-dimensional cross-linked network with high cross-linking density of the epoxy resin carbon skeleton prevents slippage of the lithium metal matrix, ensuring the dimensional stability of the epoxy resin carbon skeleton lithium metal anode under battery assembly pressure and long-term cycling. Lithium metal undergoes significant volume expansion during charging and discharging. The micropores within the epoxy resin carbon skeleton and the gaps between the fiber networks provide ample space for lithium deposition. When lithium is inserted, it preferentially fills these pores, thus buffering the overall thickness expansion of the electrode and preventing the formation of sharp dendrites on the surface due to volume expansion.
[0076] Furthermore, the modified epoxy resin carbon skeleton lithium metal anode obtained by epoxy resin carbon skeleton composite lithium metal has improved tensile strength, so that the originally flexible lithium metal no longer undergoes surface adhesion and tearing during industrial rolling and die cutting, which is more conducive to large-scale industrial production.
[0077] Other limitations regarding the epoxy resin carbon skeleton lithium metal anode are the same as those in the first embodiment above, and will not be repeated here.
[0078] Please see Figure 3 A third embodiment of the present invention provides a lithium battery 10 having the above-described epoxy resin carbon skeleton lithium metal anode 11, wherein the epoxy resin carbon skeleton lithium metal anode 11 serves as the anode of the lithium battery 10. The lithium battery further includes a positive electrode 12 and a solid electrolyte 13, wherein the solid electrolyte 13 is disposed between the positive electrode 12 and the epoxy resin carbon skeleton lithium metal anode 11.
[0079] The lithium battery 30 also includes a casing 14 for housing the epoxy resin carbon skeleton lithium metal negative electrode 11, the solid electrolyte 13, and the positive electrode 12.
[0080] The positive electrode 12 can be made of one or a combination of several of the following: layered oxide, lithium cobalt oxide (LiCoO2, LCO), spinel lithium manganese oxide (LiMn2O4, LMO), and lithium iron phosphate (LiFePO4, LFP). The solid electrolyte 13 can be made of one or a combination of several of the following: oxide solid electrolyte, sulfide solid electrolyte, polymer solid electrolyte, and halide solid electrolyte; the present invention does not limit the material. The limitations regarding the epoxy resin carbon skeleton lithium metal negative electrode 11 are the same as those in the first embodiment described above, and will not be repeated here.
[0081] The lithium battery 10 uses the epoxy resin carbon skeleton lithium metal anode 11 provided by this invention as its anode. The epoxy resin carbon skeleton lithium metal anode 11 has good tensile strength and a high content of flexible lithium metal, while also possessing good ductility, which can meet the requirements for the preparation and assembly of irregularly shaped batteries such as flexible batteries and curved batteries. The nitrogen, oxygen and other heteroatom active sites on the epoxy resin carbon skeleton of the epoxy resin carbon skeleton lithium metal anode 11 can attract lithium ions to be evenly distributed, enhancing its interface stability. The epoxy resin carbon skeleton provides sufficient space for lithium deposition, avoiding the formation of sharp dendrites on the surface due to volume expansion, thereby improving the safety and cycle stability of the lithium battery 10. The epoxy resin carbon skeleton has a rigid three-dimensional cross-linked network with high cross-linking density. The epoxy resin carbon skeleton lithium metal anode 11 can still maintain structural integrity after multiple cycles, which can effectively extend the cycle life of the lithium battery 10. The epoxy resin carbon skeleton of the epoxy resin carbon skeleton of the lithium metal anode 11 physically blocks the contact between the electrolyte and the internal lithium through its porous structure, which helps to form a more stable solid electrolyte interface film, thereby reducing side reactions, stabilizing the electrode interface, and improving the battery coulombic efficiency.
[0082] To better illustrate the superior performance of the epoxy resin carbon skeleton lithium metal anode prepared by the technical solution protected by this invention, this invention further provides the following specific experimental examples and comparative examples as specific examples of the epoxy resin carbon skeleton lithium metal anode and its preparation method claimed by this invention.
[0083] Example 1: The preparation steps of the epoxy resin carbon skeleton lithium metal anode are as follows: 1. Step S1: Preparation of epoxy resin crosslinking polymer precursor. Bisphenol A type epoxy resin E-44 and methyltetrahydrophthalic anhydride curing agent were mixed at a mass ratio of 1:0.85. The methyltetrahydrophthalic anhydride curing agent was added to the bisphenol A type epoxy resin E-44 and stirred at 100 rpm for 5 min. Degassing was performed at 100 Pa until no bubbles were generated. Then, 0.3% of the total resin mass of 2-ethyl-4-methylimidazolium was added as a catalyst. Under nitrogen protection, the mixture was pre-cured at 90℃ for 1.5 h, and then the temperature was raised to 150℃ for 3 h to continue curing, resulting in a dense epoxy resin crosslinking polymer. 2. Step S2: Preparation of epoxy resin carbon skeleton. The epoxy resin crosslinking polymer is ground into powder and placed in a tube furnace. Under a nitrogen / oxygen mixed atmosphere with a volume ratio of 97:3, the temperature is increased to 480℃ at a heating rate of 2℃ / min and carbonized at this temperature for 2.5h. The carbonized product is then acid-washed with 0.1M dilute nitric acid (soaked for 3-6h), and then washed with deionized water until the washing solution is neutral or weakly acidic. The product is then activated at 300℃ for 1h under a nitrogen atmosphere to obtain epoxy resin carbon skeleton. 3. Step S3: Epoxy resin carbon skeleton lithium metal anode composite and molding. The epoxy resin carbon skeleton obtained in step S2 is mixed with lithium metal at a mass ratio of 95:5. The mixing is carried out on a two-roll mill with the front roller speed set at 15 rpm, the front roller speed ratio to the rear roller speed ratio at 1.2:1, the front roller to rear roller gap at 1.0 mm, the mixing temperature controlled at 40℃, and the mixing time at 20 min to obtain uniform modified lithium metal. The modified lithium metal is rolled into a continuous sheet with a thickness of 0.1 mm by a cold rolling mill at room temperature, and then die-cut according to the battery model to obtain the epoxy resin carbon skeleton lithium metal anode.
[0084] Experimental Example 2: The difference from Experimental Example 1 is that the epoxy resin used in Experimental Example 2 is bisphenol F type epoxy F-51, and the mass ratio of epoxy resin to curing agent is 1:0.90.
[0085] Experimental Example 3: The difference from Experimental Example 1 is that the epoxy resin used in Experimental Example 3 is phenolic epoxy DEN431, the curing agent is diaminodiphenyl sulfone, and the mass ratio of epoxy resin to curing agent is 1:0.95.
[0086] Experimental Example 4: The difference from Experimental Example 1 is that the curing agent used in Experimental Example 4 is polyetheramine D-230, and the mass ratio of epoxy resin to curing agent is 1:0.80.
[0087] Experimental Example 5: The difference from Experimental Example 1 is that the mass ratio of epoxy resin to curing agent is 1:1.10.
[0088] Experimental Example 6: The difference from Experimental Example 1 is that the volume ratio of N2 to O2 in the carbonization atmosphere is 99:1.
[0089] Experimental Example 7: The difference from Experimental Example 1 is that the volume ratio of N2 to O2 in the carbonization atmosphere is 95:5.
[0090] Experimental Example 8: The difference from Experimental Example 1 is that the volume ratio of N2 to O2 in the carbonization atmosphere is 97:3, and the carbonization temperature is 350℃.
[0091] Experimental Example 9: The difference from Experimental Example 1 is that the volume ratio of N2 to O2 in the carbonization atmosphere is 97:3, and the carbonization temperature is 550℃.
[0092] Experimental Example 10: The difference from Experimental Example 1 is that the mass ratio of lithium metal to epoxy resin carbon skeleton is 92:8.
[0093] Experimental Example 11: The difference from Experimental Example 1 is that the mass ratio of lithium metal to epoxy resin carbon skeleton is 90:10.
[0094] Experimental Example 12: The difference from Experimental Example 1 is that the mass ratio of lithium metal to epoxy resin carbon skeleton is 97:3.
[0095] Experimental Example 13: The difference from Experimental Example 1 is that the mass ratio of lithium metal to epoxy resin carbon skeleton is 99:1.
[0096] Comparative Example 1: The difference from Experimental Example 1 is that, instead of using an epoxy resin carbon skeleton, pure lithium metal was directly rolled into a continuous sheet with a thickness of 0.1 mm at room temperature using a cold rolling mill, and then die-cut according to the battery model to obtain a lithium metal anode, which was used as a benchmark for comparison.
[0097] Comparative Example 2: The difference from Experimental Example 1 is that a pure N2 atmosphere was used for carbonization.
[0098] Comparative Example 3: The difference from Experimental Example 1 is that the mass ratio of lithium metal to epoxy resin carbon skeleton is 80:20.
[0099] Comparative Example 4: The difference from Experimental Example 1 is that no pre-curing was performed; it was directly cured at 150℃ for 4.5 hours.
[0100] Comparative Example 5: The carbon framework prepared using a dimethyl terephthalate and aliphatic diol system, and the corresponding lithium metal anode prepared by combining it with lithium metal, are detailed in the following steps: 1. The preparation of the crosslinked polymer precursor includes the following steps: The reactants are added in a molar ratio of dimethyl terephthalate: aliphatic diol = 1:1.1 (wherein the aliphatic diol includes ethylene glycol, propylene glycol, and butanediol, with a molar ratio of ethylene glycol:propylene glycol:butanediol = 1:0.6:0.4). 0.03% of the total mass of the raw materials is added as a catalyst, tetrabutyl titanate. The mixture is heated and stirred at 150°C until homogeneous. The reaction temperature is gradually increased to 180°C, and the reaction is carried out for 2 hours. A vacuum is then applied to the reaction system to reduce the ambient pressure to between 1000-5000 Pa, while simultaneously raising the temperature to 190°C. After the system stops boiling violently, the temperature is raised to 225°C and the reaction continues for 2 hours. After the reaction is complete, a polyester oligomer is obtained. The above-mentioned polyester oligomer and trimethyl citrate were weighed at a molar ratio of 1:1.05, and then 0.02% by mass of tetrabutyl titanate catalyst was added. Nitrogen gas was introduced to ensure an inert atmosphere for the reaction. The mixture was stirred, purged with nitrogen, and heated to 180°C, then slowly increased to 200°C and reacted for 2 hours. The temperature was then further increased to 220°C, and a vacuum was applied to gradually reduce the reaction environment from atmospheric pressure to below 100 Pa. Once the preset conditions were met, the reaction was stopped to obtain the crosslinked polymer precursor.
[0101] 2. The preparation of the carbon skeleton includes the following steps: The cross-linked polymer precursor obtained in the previous step is first vacuum dried at 80℃ for 4h to remove residual unreacted small molecule impurities, and then placed in a furnace for medium-low temperature carbonization. The ambient atmosphere is a mixture of nitrogen and oxygen, with the oxygen volume fraction accounting for 5%. The temperature is increased to 450℃ at a heating rate of 1℃ / min, and held for 30min after reaching the target temperature. The material after medium-low temperature carbonization is then acid-washed with dilute nitric acid (acid concentration of 0.1mol / L, soaking time of 3-6h), and washed with deionized water until the washing solution is neutral or weakly acidic. Finally, the material is activated at low temperature (atmosphere of N2, maintained at 300℃ for 1h) to obtain the carbon skeleton.
[0102] 3. The preparation of the lithium metal anode includes the following steps: Lithium metal and carbon skeleton are mixed in a 90:10 mass ratio in a two-roll mill. The front roller speed is 15 rpm, the front roller to rear roller speed ratio is 1.2:1, the mixing temperature is 40℃, the roller gap is 1 mm, and the mixing time is 20 min. The modified lithium metal after mixing is cold-rolled into a continuous sheet of 0.1 mm, and then die-cut to the size required for lithium batteries, thus producing the lithium metal anode.
[0103] The tensile strength and elongation at break of the lithium metal anodes obtained in the above experimental examples and comparative examples were measured. The lithium metal anodes obtained in the above experimental examples and comparative examples were assembled with the positive electrode and solid electrolyte into lithium batteries, and the battery cycle life and the number of battery cycles with 20% capacity loss were measured.
[0104] Tensile strength (Rm) refers to the maximum engineering stress that a lithium metal sample can withstand before fracture under uniaxial tensile load. The calculation formula is: Rm=Fm / S0, where: Fm: the maximum tensile force before the sample fractures (unit: N); S0: the original cross-sectional area of the sample (unit: mm², which needs to be accurately calculated according to the sample shape).
[0105] Elongation at break ( A () refers to the percentage elongation of the gauge length portion of the lithium metal anode after it breaks, relative to the original gauge length. The calculation formula is: A =[(L u -L0) / L0]×100%, where L u L0 is the gauge length after fracture, and L1 is the original gauge length. During testing, the specimen is mounted on the testing machine, and an initial gauge length (L0) is set. Then, the testing machine applies a tensile force at a constant rate until the specimen fractures. During the test, the equipment simultaneously records the force and the gauge length after fracture (L0). u (Data).
[0106] Under constant charge and discharge conditions with a current density of 1 mA / cm², the cycle life of the lithium batteries in the experimental example and the comparative example was tested. With a capacity loss of 20% as the cutoff condition, the number of complete charge and discharge cycles completed by the lithium batteries was determined.
[0107] Table 1. Performance data of experimental examples and comparative examples
[0108] As shown in Examples 1-13, the epoxy resin carbon skeleton lithium metal anode prepared by the method of this invention has a tensile strength of 7 MPa-12 MPa and an elongation at break of 10.5%-20.1%. When the epoxy resin carbon skeleton lithium metal anode prepared by this invention is applied to lithium batteries, the average cycle life of the lithium battery can reach over 1000 hours, with a better example reaching over 1200 hours; the battery cycle count can reach up to 1136 cycles when the capacity loss is 20%. In Comparative Example 1, the pure lithium metal anode without epoxy resin carbon skeleton modification has extremely low tensile strength (1.4 MPa), poor rigidity, and weak resistance to plastic deformation; its overall performance is significantly inferior to that of Examples 1-13.
[0109] As shown in Examples 1-4, different epoxy resin-curing agent systems can all prepare effective reinforced carbon skeletons. Specifically, Examples 1 and 2 used bisphenol-based epoxy resin and anhydride curing agents, Example 3 used phenolic epoxy resin and an amine curing agent, and Example 4 used bisphenol-based epoxy resin and an amine curing agent. The tensile strength and elongation at break of the epoxy resin carbon skeleton lithium metal anodes of Examples 1 and 2 were higher than those of Examples 3 and 4. The battery cycle life and the number of cycles with a 20% capacity loss of the lithium batteries of Examples 1 and 2 were also higher than those of Examples 3 and 4. The epoxy resin carbon skeleton prepared by the bisphenol-based epoxy resin and anhydride curing agent system exhibited more balanced and superior mechanical and electrochemical properties.
[0110] As shown in Experiments 1, 10-13, and Comparative Example 3, the composite ratio of lithium metal to epoxy resin carbon skeleton exhibits the best overall performance in the range of 90:10 to 95:5. In Experiment 12, the mass ratio of lithium metal to epoxy resin carbon skeleton was 97:3. Compared with Experiment 1, the content of epoxy resin carbon skeleton was slightly lower. The mechanical properties and cycle stability of the epoxy resin carbon skeleton lithium metal anode in Experiment 12 were lower than those in Experiment 1, but still better than those in Comparative Example 3. In Experiment 13, the mass ratio of lithium metal to epoxy resin carbon skeleton in Experiment 12 was 99:1. This mass ratio is close to the lower limit of the lithium metal to epoxy resin carbon skeleton ratio in this invention. The low proportion of epoxy resin carbon skeleton slightly reduces the reinforcing effect and tensile strength. Relying solely on the toughness of lithium metal itself, the elongation is relatively high, and the epoxy resin carbon skeleton lithium metal anode can still maintain excellent cycle performance. As shown in Comparative Example 3, an excessively high composite ratio of lithium metal and epoxy resin carbon skeleton will severely impair the ductility and lithium battery performance of the epoxy resin carbon skeleton lithium metal anode. In Comparative Example 3, the composite ratio of lithium metal and epoxy resin carbon skeleton is 80:20. Due to the excessively high content of epoxy resin carbon skeleton, the hard and brittle reinforcing phase of the epoxy resin carbon skeleton lithium metal anode increases, and the tensile strength continues to rise. However, the proportion of flexible lithium metal decreases, the overall ductility of the epoxy resin carbon skeleton lithium metal anode deteriorates, the elongation at break decreases, and the cycle stability of the epoxy resin carbon skeleton lithium metal anode decreases significantly.
[0111] As shown in Experiments 1 and 8-9, carbonization temperature affects the structure of the epoxy resin carbon skeleton, which in turn affects the performance of the epoxy resin carbon skeleton lithium metal anode and the lithium battery. The carbonization temperature in Experiment 8 was slightly lower, resulting in lower pyrolysis of the epoxy resin crosslinking polymer during carbonization. This led to a looser epoxy resin carbon skeleton structure compared to that in Experiment 1, with a slight decrease in tensile strength but better flexibility and higher elongation. The looser epoxy resin carbon skeleton structure resulted in weaker interfacial bonding with lithium metal, leading to a slight decrease in the battery cycle performance of the obtained epoxy resin carbon skeleton lithium metal anode. Compared with Experiment 1, Experiment 9 had a slightly higher carbonization temperature, which increased the graphitization degree of the epoxy resin carbon skeleton. The epoxy resin carbon skeleton structure became harder and more brittle. The tensile strength of the epoxy resin carbon skeleton lithium metal anode was still acceptable, but the elongation at break was reduced. The slightly higher carbonization temperature may have caused excessive escape of heteroatoms such as nitrogen, oxygen, and sulfur, resulting in a reduction in active sites and weakening the interfacial bonding between the epoxy resin carbon skeleton and lithium metal. As a result, the cycle performance of the obtained epoxy resin lithium metal anode was slightly reduced.
[0112] Compared with Experimental Example 1, in Experimental Example 5, the mass ratio of epoxy resin to curing agent was 1:1.10, with a slight excess of curing agent. The remaining curing agent molecules in the reaction system could not react with the epoxy resin to form an effective bond, resulting in a decrease in crosslinking density. The obtained epoxy resin carbon skeleton was prone to cracking and a decrease in strength. Ultimately, the tensile strength and elongation at break of the obtained epoxy resin carbon skeleton lithium metal anode decreased, and the cycle performance also decreased.
[0113] As shown in Experiments 1, 6, and 7, and Comparative Example 2, introducing an appropriate amount of oxygen into the carbonization atmosphere is crucial for enhancing the surface active sites of the epoxy resin carbon skeleton. In Comparative Example 2, under a pure nitrogen carbonization atmosphere, a large number of oxygen- and nitrogen-containing groups in the epoxy resin carbon skeleton directly decompose, resulting in a dense and brittle epoxy resin carbon skeleton structure. Consequently, the tensile strength and elongation at break of the corresponding epoxy resin carbon skeleton lithium metal anode decrease, significantly degrading the performance of the lithium battery. In Experiments 6 and 7, the volume fraction of oxygen in the carbonization atmosphere is within the range of 1%-5%, which effectively preserves the active sites in the epoxy resin carbon skeleton. In Experiment 6, the volume ratio of nitrogen to oxygen is 99:1. The mechanical properties and cycle performance of the epoxy resin carbon skeleton lithium metal anode in Experiment 6 are better than those in Comparative Example 2, indicating that even at lower oxygen content, it is still more effective than pure nitrogen.
[0114] As demonstrated by Experimental Example 1 and Comparative Example 4, the pre-curing process is crucial for improving the performance of the epoxy resin carbon skeleton during the preparation of the epoxy resin crosslinking polymer. In Comparative Example 4, the epoxy resin carbon skeleton was prepared without pre-curing. A large number of active groups in the reaction system did not have enough time to react, resulting in incomplete reaction. Consequently, the crosslinking density of the obtained epoxy resin carbon skeleton decreased, and the mechanical properties and cycle stability of the lithium battery anode obtained after the epoxy resin carbon skeleton was combined with lithium metal were significantly reduced.
[0115] Experimental Example 11 uses the epoxy resin carbon skeleton of the present invention to prepare an epoxy resin carbon skeleton lithium metal anode by compositing with lithium metal; Comparative Example 5 uses a carbon skeleton prepared by a system of dimethyl terephthalate and aliphatic diols to prepare a lithium metal anode by compositing with lithium metal. Compared with Comparative Example 5, the epoxy resin carbon skeleton lithium metal anode of Experimental Example 11 has better mechanical properties and superior electrical performance of the lithium battery. When the addition ratio of lithium metal to carbon skeleton is consistent, the tensile strength of the epoxy resin carbon skeleton lithium metal anode of Experimental Example 11 of the present invention is increased by 27.6%, and the cycle life of the lithium battery is increased by 38.8%, resulting in a significant improvement in the performance of the lithium battery.
[0116] Based on the above experimental examples and comparative examples, it can be seen that the tensile strength of the epoxy resin carbon skeleton lithium metal anode prepared by the method of the present invention is effectively improved, thus effectively improving the mechanical properties of the epoxy resin carbon skeleton lithium metal anode, and the resulting lithium battery exhibits excellent cycle performance. The epoxy resin carbon skeleton lithium metal anode of the present invention comprises lithium metal and an epoxy resin carbon skeleton. The epoxy resin carbon skeleton has abundant reaction sites containing oxygen and nitrogen, which can bind with lithium metal, enhancing the interfacial bonding between the epoxy resin carbon skeleton and lithium metal. The rigid three-dimensional cross-linked network with high cross-linking density improves the tensile strength and structural stability of the epoxy resin carbon skeleton lithium metal anode, achieving synergistic optimization of strength and rigidity. As a three-dimensional reinforcement, the epoxy resin carbon skeleton achieves stress transfer through interfacial interaction, transferring most of the applied tensile load to the carbon skeleton, significantly improving the tensile strength of the epoxy resin carbon skeleton lithium metal anode. The rigid three-dimensional cross-linked network with high cross-linking density of the epoxy resin carbon skeleton can prevent slippage of the lithium metal matrix, enabling the epoxy resin carbon skeleton lithium metal anode to maintain dimensional stability under battery assembly pressure and long-term cycling.
[0117] The foregoing has provided a detailed description of an epoxy resin carbon skeleton lithium metal anode, its preparation method, and a lithium battery disclosed in the embodiments of the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention. Any modifications, equivalent substitutions, and improvements made within the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an epoxy resin carbon skeleton lithium metal anode, characterized in that, Includes the following steps: Epoxy resin and curing agent are mixed at a mass ratio of 1:(0.8-1.2), and a catalyst with a mass content of 0.2%-0.5% of the epoxy resin content is added. The mixture is pre-cured at 80℃-120℃ for 1h-3h under an inert atmosphere, and then the temperature is raised to 140℃-180℃ for 2h-5h to obtain an epoxy resin crosslinked polymer. The epoxy resin includes any one or a combination of bisphenol F type epoxy resin, phenolic epoxy resin, and bisphenol A type epoxy resin. The epoxy resin crosslinking polymer was carbonized in a carbonizing atmosphere at a heating rate of 1℃ / min-5℃ / min to 300℃-600℃ for 1h-4h. The carbonized product was then acid-washed with 0.1M-1M dilute nitric acid, followed by water washing, and activated at 250℃-400℃ for 1h-3h in an inert atmosphere to obtain the epoxy resin carbon skeleton. The carbonizing atmosphere was a mixture of nitrogen and oxygen, with an oxygen volume fraction of 1%-5%. Modified lithium metal is obtained by mixing lithium metal with epoxy resin carbon skeleton in a certain proportion, and the modified lithium metal is made into epoxy resin carbon skeleton lithium metal anode.
2. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 1, characterized in that, The curing agent includes any one of methyltetrahydrophthalic anhydride, diaminodiphenyl sulfone, and polyetheramine.
3. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 1, characterized in that, The specific process of mixing epoxy resin and curing agent involves adding the curing agent to the epoxy resin, stirring at 100rpm-200rpm for 3min-5min, and then performing degassing treatment at 100Pa-200Pa.
4. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 1, characterized in that, The catalyst includes any one or a combination of imidazole catalysts and amine catalysts.
5. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 1, characterized in that, The modified lithium metal is obtained by mixing the lithium metal and the epoxy resin carbon skeleton in a two-roll mill at a mass ratio of (90-99):(1-10).
6. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 5, characterized in that, The two-roll open mill includes a front roll and a rear roll. The front roll rotates at 10 rpm to 20 rpm, and the speed ratio between the front roll and the rear roll is (1.1-1.5):1; and / or the roll gap between the front roll and the rear roll is 0.5 mm to 2 mm.
7. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 5, characterized in that, The mixing process is carried out at a temperature of 30℃-60℃ for a time of 10min-30min.
8. The method for preparing an epoxy resin carbon skeleton lithium metal anode as described in claim 1, characterized in that, The modified lithium metal is cold-rolled into a sheet with a thickness of 0.05mm-0.5mm, and then die-cut to obtain an epoxy resin carbon skeleton lithium metal anode.
9. An epoxy resin carbon skeleton lithium metal anode, characterized in that: The epoxy resin carbon skeleton lithium metal anode is prepared by the epoxy resin carbon skeleton lithium metal anode preparation method according to any one of claims 1-8, wherein the epoxy resin carbon skeleton lithium metal anode comprises lithium metal and epoxy resin carbon skeleton, and the mass ratio of lithium metal to epoxy resin carbon skeleton is (90-99):(1-10); and / or, the tensile strength of the epoxy resin carbon skeleton lithium metal anode is 7MPa-12MPa.
10. A lithium battery, characterized in that: The lithium battery includes a positive electrode, an electrolyte, and an epoxy resin carbon skeleton lithium metal negative electrode as described in claim 9.
Citation Information
Patent Citations
Lithium metal negative electrode and preparation method thereof, and lithium battery
CN120933292B